1977
DOI: 10.1159/000207893
|View full text |Cite
|
Sign up to set email alerts
|

Antihaemophilic Factor A Activity, F VIII-Related Antigen and von Willebrand Factor in Hepatic Cirrhosis

Abstract: F VIII activity, F VIII-related antigen and von Willebrand factor were measured in 46 patients with hepatic cirrhosis and in 30 normal individuals. These parameters were significantly higher in hepatic cirrhosis than in the controls. Linear relationships between F VIII activity and F VIII-related antigen and between F VIII-related antigen and von Willebrand factor were found in patients with hepatic cirrhosis as well as in normal individuals. However, in both groups no relationship between F VIII activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…A similar relationship has been reported in normal subjects in basal condi tions, at least between F VIII:C and F VIIIR:AG [1,3,7,11,18], while there are discordant reports for F VIIIR:RCof [1,5,21], The significant correlations between the F VIII-VWF components found in our cases after VO, notwithstanding their striking and heterogeneous rise, are in agreement with previous observations made using stimuli such as catecholamine administration [7,12] and physical exercise [2,7,17], A highly significant activation of fibrino lysis was recorded following VO, the results of ELT and DBCLT being strictly correlated. This finding supports the belief that the two methods basically measure the same phe nomenon, the release of plasminogen activa tor.…”
Section: Discussionsupporting
confidence: 85%
“…A similar relationship has been reported in normal subjects in basal condi tions, at least between F VIII:C and F VIIIR:AG [1,3,7,11,18], while there are discordant reports for F VIIIR:RCof [1,5,21], The significant correlations between the F VIII-VWF components found in our cases after VO, notwithstanding their striking and heterogeneous rise, are in agreement with previous observations made using stimuli such as catecholamine administration [7,12] and physical exercise [2,7,17], A highly significant activation of fibrino lysis was recorded following VO, the results of ELT and DBCLT being strictly correlated. This finding supports the belief that the two methods basically measure the same phe nomenon, the release of plasminogen activa tor.…”
Section: Discussionsupporting
confidence: 85%
“…Liver disease is frequently associated with abnormalities of the blood coagulation system with a reduction in concentration of many of the individual clotting factors (1,2). Several studies have shown, however, that the level of factor VIII is increased in liver disease (3,4,5). Factor VIII circulates as a complex of two proteins (6), the factor VIII procoagulant protein (VIIIC), and the factor VIII related antigen protein (VIIIRAg) which contains von Willebrand factor (VIIIvWF).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore because of the necrosis of the liver cells, the hemodynamic changes due to ex panded collaterals in the presence of im paired clearance of activated factors could trigger off disseminated intravascular coagu lation (DIC), inducing bleeding in liver pa tients [21,22,28]. In acute hepatic failure the incidence and magnitude of intravascular co agulation and its relation to the severity of bleeding and prognosis has been assessed [13], Subsequently, in hepatic cirrhosis and in other diseases with liver involvement, evi dence of the relationship between a hypercoagulable state and a significant increase or decrease of most significant parameters in this condition has been reported [1,10,14,18,27], To verify the relationship of bleeding to either a hypercoagulability condition or the severity of hepatic failure, we evaluated fac tor VIII:C (F VIII:C), factor VIIIR:AG (F VIIIR:AG), factor VIII AG/C ratio (F VIII AG/C) and serum fibrin-fibrinogen degrada tion products (FDP) in a group of patients with advanced liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%